The Effects of Cryogenic Process on the AISI M2 Punch Materials and on the Hole Edge Geometry of the DIN EN 10111-98 Sheet Metal Control Arm Parts - Yusuf Arslan (Advances in Materials Science and Engineering)
In this study, not only the effects of cryogenic processing on the wear of AISI M2 punches but also the effects of punch wear on the hole edge geometry of DIN EN 10111-98 sheet metal control arm parts were investigated. The hole geometry changes are generally associated with punch wear and process parameters. Piercing operations were performed using eccentric press on 2.5-mm-thick sheet metal control arm parts with circular and slot AISI M2 tool steel punches. The punches were traditionally heat treated. The others were cryogenically treated at −145°C in addition to the conventional heat treatment. Weight losses were measured for punch wear assessments; furthermore, SEM and OM images were analyzed. The hole edge geometries of the selected parts were measured with a contour measuring machine in the specified number of blanks. So, no damage was done to the products for measurements. The cryogenic process resulted in a significantly low amount of retained austenite and caused uniformly distributed thin carbide precipitates. Reduction of retained austenite and formation of fine carbide particles led to increase in hardness values. It was found that untreated circular punch wear weight losses were approximately 40% higher than those of cryogenically treated samples. The untreated slot punch change rate was about 106% higher than that of the cryogenically treated samples. The wear process during the punching was faster and greater for the untreated punches. Fatigue microcracks were more common at the cutting edge of the untreated punches. However, abrasive wear was generally observed in cryogenically treated punches. The edge geometry values in the circular holes were at least two times higher than those in the slot holes of untreated samples. At the end of the industrial piercing process, it was determined that the M2 tool steel punch wear rates were decreased by cryogenic treatment, and the size changes of the hole geometry of the punches of the DIN EN 10111-98 control arm parts were more economic and with a better quality.